Estudio de prefactibilidad para la instalación de una fábrica de elaboración de estearato de zinc para aplicación en la industria de caucho y plásticos - Palacios Masson, Diego Alejandro (2018)
The present study evaluates the installation of a zinc stearate facility in Peru technically, economically, and market viability. This facility will focus on Peruvian market, mainly in the rubber and plastics industry, where it has a number of applications such as stabilization, unmolding, and even rubber vulcanization. Peru is an importan zinc producer and in this study it is shown the feasibility of transforming natural resources into industrial products which can be seized by Peruvian industry, being able to compete with other product that are being imported due to lack of offer. This document starts with the objectives and scope of the study and the presentation of zinc stearate. In the next place, the market viability is analyzed, showing that the product could be sold at $ 3,74 per kilogram (sold in 20 kg sacks), and have a demand surrounding 9 000 sacks per year. Under these circumstances, EBITDA would be rounding 23,5%; however, some strong reasons are presented that the market can possibly expand almost three times. After the analylis of demand, the study continues with the location study, plant capacity, project engineering, where the manufacturing process, equipment, and space requirements are explained. Then study continues with the personnel requirements for the facility to work normally, economic and financial evaluation that details cash flows and scenario analysis that could possibly occur in the Peruvian market. Finally, the study concludes with a social impact analysis considering the facility´s surroundings.